RANCANG BANGUN PROTOTYPE SISTEM KEAMANAN SEPEDA MOTOR BERBASIS E-SIM MENGGUNAKAN RFID - Nur Faqih, Mochamad; Budiyono, Budiyono; Prasetyo, Imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
The case of motorcycle theft is not a new or common thing in the ears of the public and the world of the Indonesian National Police or the Indonesian National Police. Motorcycle theft cases can happen at any time. In accordance with the regulations of the Indonesian National Police as stated in Article 18 Paragraph 1 of Law no. 14 of 1992 which reads